Paratrypanosoma is a novel early-branching trypanosomatid - Skalický, Tomáš (Jihočeská univerzita, 2014)
The kinetoplastids are a widespread and important group of single-celled eukaryotes, many of which are devastating parasites of animals, including humans. We have discovered a new insect trypanosomatid in the gut of Culex pipiens mosquitoes. Glyceraldehyde-3-phosphate dehydrogenase- and SSU rRNA-based phylogenetic analyses show this parasite to constitute a distinct branch between the free-living Bodo saltans and the obligatory parasitic clades represented by the genus Trypanosoma and other trypanosomatids. From draft genome sequence data, we identified 114 protein genes shared among the new flagellate, 15 trypanosomatid species, B. saltans, and the heterolobosean Naegleria gruberi, as well as 129 protein genes shared with the basal kinetoplastid Perkinsela sp. Individual protein phylogenies together with analyses of concatenated alignments show that the new species, here named Paratrypanosoma confusum n. gen., n. sp., branches with very high support at the base of the family Trypanosomatidae. P. confusum thus represents a long-sought-after missing link between the ancestral free-living bodonids and the derived parasitic trypanosomatids. Further analysis of the P. confusum genome should provide insight into the emergence of parasitism in the medically important trypanosomatids.
Paratrypanosoma is a novel early-branching trypanosomatid
Keywords: Paratrypanosoma; insect trypanosomatid; genome sequencing; phylogenetics; Paratrypanosoma; insect trypanosomatid; genome sequencing; phylogenetics